Safety Clearance and Artifact Testing of a Nitinol Breast Biopsy Clip in an Ultra-High Resolution (7 Tesla) Magnetic Resonance Imaging Environment - William Dong; Kanchna Ramchandran; Adam E. Galloy; Marco A. Nino; Marla Kleingartner; John Piaszynski; Madhavan L. Raghavan; Sneha Phadke; Vincent A. Magnotta (Indian Journal of Radiology and Imaging)
Background The lack of safety clearance of several metallic breast biopsy clips in 7 Tesla (T) poses a significant hurdle to using advanced magnetic resonance imaging (MRI) techniques in clinical management or cancer research.